Mapping the landscape of e-learning research: a bibliometric analysis / Norliza Muhamad Yusof ... [et al.] - Muhamad Yusof, Norliza; Sapini, Muhamad Luqman; Mohd Nasir, Muhammad Zulqarnain; Mohd Salim, Mohd Nur Fitri (UiTM Press, 2024)
This research conducts a comprehensive bibliometric analysis of academic publications on e-learning, aiming to gain perspectives on the state of the field, and the emergence of patterns within this field of study. A systematic search was conducted in the Scopus database, yielding 1983 documents related to e-learning. The network analysis focused on keyword distribution, country representation, and co-authorship using VOSViewer software and weighted degree centrality. The keyword analysis revealed "e-learning" as the dominant and central theme, highlighting its significance in the research domain. The emergence of "Covid-19" as a widely used keyword for searches implied that the pandemic affected e-learning activities. Moreover, the representation of institutions from diverse countries showcased the global interest in e-learning research, fostering potential cross-cultural collaborations. Additionally, the increasing trend in e-learning research publications over the years indicated the growing importance of digital education. The interdisciplinary nature of e-learning research, spanning Computer Science, Social Sciences, Engineering, and Medicine, underscored the field's diverse perspectives. Furthermore, the Social Network Analysis unveiled collaborative networks of co-cited authors, regions, and keywords, illuminating the interconnectedness within the e-learning research community. The findings contribute to a better understanding of the e-learning research landscape, facilitating informed decision-making for researchers, educators, policymakers, and institutions. Likewise, the analysis provides valuable insights for future research directions, enabling advancements in e-learning practices and fostering innovation in the digital age.